564 Controversial role of intracardiac eletrophysiology study in Brugada syndrome: analysis of a single-centre retrospective cohort study. (8th December 2021) - Licciardello, Claudio; Marazzato, Jacopo; Golino, Michele; Seganfreddo, Francesca; Matteo, Federica; Giovenzana, Fulvio Lorenzo Francesco; Franzosi, Cinzia; Genoni, Paola; De Ponti, Roberto
Abstract: Aims: According to European guidelines, aborted sudden cardiac death (SCD) in Brugada syndrome (BrS) is regarded as a I class recommendation for secondary prevention implantable cardioverter defibrillator (ICD). However, the risk stratification of BrS patients for primary prevention ICD still represents a clinical conundrum. Although intracardiac electrophysiology (EP) study proved useful for the selection of high-risk patients in this setting. Therefore, aim of this study was to assess all clinical and EP variables associated with the induction of VA at EP study and the rate of appropriate/inappropriate ICD interventions and/or clinical SCD events in these patients occurring at follow-up. Methods and results: From 2001 to 2021, all EP studies performed in symptomatic/asymptomatic patients (46 ± 14 years, M 88%) with/without family history of SCD spontaneous/drug-induced type I pattern (TIP) on ECG and no spontaneous ventricular arrhythmias were retrospectively considered at our study centre. Clinical variables, BrS pattern, EP study data (including right ventricular site and type of stimulation protocol), and ICD interventions (DC-shocks or Anti-Tachycardia Pacing events, ATP) and/or SCD events occurring at follow-up were all evaluated. EP study was deemed positive for any polymorphic VA induced during programmed ventricular stimulation; non-sustained episodes included. ICD was routinely implanted in all patients with a positive EP study. Follow-up data were detected by the collection of medical and home-monitoring recordings at study-site level. Follow-up data were available in 50 patients (9 ± 6 years on average). Patients were generally young with few cardiovascular comorbidities. SCD history was known in 21 (42%) with a significant number of asymptomatic patients (48%). Br patterns were equally distributed in the investigated population (spontaneous and drug-induced TIP in 52% and 48%, respectively) and AF history was fairly common (16%). In the study population, EP study tested positive in 30 patients (60%): spontaneous TIP ( P  = 0.0518), few extrastimuli during programmed ventricular stimulation ( P  = 0.0015), and right ventricular stimulation at the apical site ( P ≤ 0.0001) were the only variables to be clearly associated with a positive EP study in the appraised patients. At follow-up, appropriate ICD shocks were documented in 4 out of 30 implanted patients (13%) at generally 5 ± 7 years from EP study evaluation. Although three ICD interventions (75%) occurred in patients with spontaneous TIP, one patient with drug-induced TIP pattern and positive EP study referred to Emergency Department for unrelenting VT storm after roughly 13 years from ICD implantation. Inappropriate ICD interventions for fast rate AF were detected in 10% of cases. Finally, no SCD events were documented at follow up in patients with a negative EP study. Conclusions: In a retrospective analysis, EP study proved useful in the risk stratification of SCD in BrS patients. A few ventricular extrastimuli delivered at the right ventricular apex seem sufficient to prompt the induction of life-threatening VA in high-risk BrS patients during EP study. Moreover, in this setting, a negative EP study seems protective against the development of VA/SCD events at follow-up. However, not only is spontaneous TIP associated with an increased risk of arrhythmic death, but a drug-induced TIP, generally regarded as a low-risk condition, might also be associated with a long-term hazard of SCD in these patients.